A new protist literacy assessment for university students - Hardianto, Hardianto; Mahanal, Susriyati; Susanto, Hendra; Prabaningtyas, Sitoresmi; Zubaidah, Siti (International Journal of Evaluation and Research in Education (IJERE), 2025)
Protists are organisms that have close involvement with student life, especially in maintaining the balance of ecosystems on earth. Literacy instruments about protists are important to develop because students need to know the relationship between protists and life. This instrument was developed because there is no specific instrument to measure student protist literacy. The purpose of this study is to develop a new protist literacy assessment (N-PLA) for university students. The N-PLA development process consists of three stages, namely, i) dimension development, item development, and expert validation; ii) exploratory factor analysis (EFA), content validity, and data reduction; iii) internal consistency through confirmatory factor analysis (CFA). The results of the study found seven dimensions of protist literacy with a total of 36 items: conceptual knowledge (CnK) (7 item), relation information (RlI) (6 item), fact evaluation (FcE) (5 item), real solution (RlS) (5 item), argument identification (ArI) (3 item), self-confidence (S-C) (4 item), and scientific value (ScV) (6 item). The developed N-PLA has a relationship between dimensions and items based on EFA and CFA test results. N-PLA has two types of instruments, namely by using tests and questionnaires to be able to measure the cognitive and affective of students. N-PLA is recommended as a measuring tool that can measure the protist literacy of university students. The results of measuring student’s protist literacy become a reference in empowering students protist literacy in the learning process in university.